In Vitro Biomechanical Study of Epidural Pressure during the Z-shape Elevating-Pulling Reduction Technique for Cervical Unilateral Locked Facets. Issue 5 (4th July 2019) - Shao, Xinwei; Zeng, Jican; Chen, Yuchun; Wu, Lixian; Wang, Xinjia
ABSTRACT: Objective : To analyze the mechanism of the halo vest-assisted Z-shape elevating-pulling reduction technique for cervical unilateral locked facets, and confirm the safety of the spinal cord under the epidural pressure that occurs during the reduction process. Methods : Eleven osteoligamentous whole coronal and cervical spine specimens were established as skull-neck-thorax models of cervical unilateral locked facets at the C5/6 level. The halo vest-assisted Z-shape elevating-pulling reduction technique was then applied to reduce the locked facets. The changes in the epidural pressure in five cervical positions (cervical physiological curvature, cervical lateral bending, cervical unilateral locked facets, cervical unilateral perched facets, and reduction) were measured by a pressure sensor during the reduction procedure. The models simultaneously underwent multi-angle radiographic examination and CT scanning. Results : Successful closed reduction was achieved via the halo vest-assisted Z-shape elevating-pulling reduction technique in all 11 models. The epidural pressure in the cervical unilateral locked facets position was significantly higher than that in the other four cervical positions (P < 0.005). There was no significant difference in the epidural pressures measured during cervical lateral bending, cervical unilateral perched facets, and reduction. Conclusions : Maximum epidural pressures were measured in the position of cervical unilateral locked facets. The halo vest-assisted Z-shape elevating-pulling reduction technique achieved spinal decompression without causing secondary spinal cord injury. The halo vest-assisted Z-shape elevating-pulling reduction technique is safe and effective, and has a high success rate of reduction.